Learning the Book of Ta'lim Al-Muta'allim at the Islamic Boarding School - Istiqamah, Resi Nurul; Putra, Andre Yuanda; Nasra, Arina; Guspita, Rosi (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2024)
This study aims to determine the planning, implementation and evaluation of learning the Ta'lim Al-Muta'allim Book at the Nurul Yaqin Ringan-ringan Islamic Boarding School, Padang Pariaman Regency. This study uses a qualitative method with a field research type. Data were taken from six informants through direct interviews using a set of interview protocols. The informants involved were selected using a nonprobability sampling technique, namely snowball sampling, from the head of the Islamic Boarding School, deputy head of the boarding school, subject teachers of the book and three students. All interview data obtained were analyzed using the Milles & Hubberman Analysis Interactive Model technique. The research findings found that the planning, implementation and evaluation of learning the Ta'lim Al-Muta'allim book carried out at the Nurul Yaqin Ringan-ringan Islamic Boarding School, Padang Pariaman Regency has a unique way so that students can understand and practice the contents of the Ta'lim Al-Muta'allim book in everyday life. This study has revealed the planning, implementation and evaluation of learning the Ta'lim Al-Muta'allim Book used in the learning process at the Islamic boarding school. In addition, the results of this study can be used as a reference for educational institutions and teachers in implementing the learning of the Ta'lim Al-Muta'allim book.